The long-term effects of different telerehabilitation programs on respiratory, exercise, and activity-related parameters in COVID-19 survivors: a randomized controlled trial in Türkiye - Abdurrahman Tanhan; Aysel Ozer; Eren Timurtaş; Ayşe Batirel; Mine Polat (James Cook University, 2024)
Introduction: The long-term outcomes of different telerehabilitation gains for discharged COVID-19 patients are largely uncertain, and this point needs to be explored. This study aimed to research the effectiveness of telerehabilitation and compare the long-term results of videoconferencing-guided synchronous telerehabilitation and mobile application-guided asynchronous telerehabilitation programs, as well as determine the correlation between clinical and hemodynamic parameters. Methods: Exercise programs including aerobic exercises, strengthening exercises, and pulmonary exercises were given to COVID-19 patients discharged from the Kartal Dr. Lütfi Kirdar City Hospital in Istanbul, Türkiye between August 2021 and January 2022, by videoconferencing or mobile application telerehabilitation. All patients underwent programs three times per week for 8 weeks. Lower extremity strength and functional status were assessed using a 30-second sit-to-stand test (30 s STS); physical activity level was assessed using the International Physical Activity Questionnaire short form (IPAQ); pulse oximetry was used to determine oxygen saturation and heart rate; and dyspnea and fatigue were assessed using a modified Borg Rating of Perceived Exertion Scale. Baseline, post-treatment, and long-term data were analyzed. Results: A total of 27 patients completed the study. Significant improvement was seen in all parameters in long-term results with telerehabilitation programs (p<0.05). Especially in the between-group effect at rest (p=0.031) and post-exertion oxygen saturation (p=0.004), there were significant differences in favor of videoconferencing. Oxygen saturation was negatively correlated with dyspnea and fatigue (p<0.05). Post-exercise, dyspnea showed a moderate positive correlation with fatigue (r=0.582, p=0.001) and heart rate (r=0.412, p=0.033), while it exhibited a moderate negative correlation with 30 s STS (r=-0.424, p=0.027) and IPAQ (r=-0.401, p=0.038). Conclusion: Both methods generally provide positive gains in clinical and hemodynamic parameters, but the videoconferencing results were slightly better. Saturation at rest and dyspnea after exertion can provide a brief prediction about the cardiopulmonary system. Our findings are important for individuals who have access problems to the clinic and city center, and can be used for follow-up and treatment approaches.